Effects Of Information Digitalization And Social Media Adoption On Financial Performance In Indonesia State Owned Enterprises - Paul Usmany; Hartina Husein; Trisye Natalia Kilay; Ribka Shintia Febriarti Bonara; Amelia Josefin Viotty Radianto (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
In the era of digital transformation, State-Owned Enterprises (SOEs) face pressure to improve transparency, stakeholder engagement, and financial performance through information digitization and the use of social media. However, the effectiveness of these digital initiatives in increasing company value remains unclear. This study aims to empirically examine the effect of information digitization and social media use on the financial performance of SOEs in Indonesia. This study uses a quantitative approach with secondary data from annual financial reports and companies, and is analyzed using the MANOVA test. The analysis of 32 SOEs in Indonesia shows that information digitization has no significant effect on financial performance. Conversely, social media use has a positive and significant effect, indicating that active engagement through digital platforms can improve interaction with stakeholders and public perception, ultimately contributing to improved financial performance. These findings emphasize the importance of strategic social media adoption as a driver of company performance, while information digitization alone is not capable of delivering a tangible financial impact.